Advancing therapeutic target discovery in pulmonary diseases: evolution and application of space exploration technologies - Yang, Bo; Zheng, Quan; Li, Guozheng; Liao, Bingnan; Lin, Zhongxiao; He, Hao (Frontiers in Cell and Developmental Biology, 2025)
Epigenetic alterations are associated with various pulmonary diseases. In recent years, the concept of epigenetic inheritance influenced by spatial variations has garnered increasing attention. Alterations in three-dimensional (3D) chromatin architecture have been demonstrated to play a crucial role in regulating gene expression and influencing the pathogenesis and progression of lung-related diseases. Techniques such as high-throughput chromosome conformation capture (Hi-C) have emerged as powerful tools for detecting spatial chromatin conformational changes. In this review, we summarize key targets identified through Hi-C and related methodologies in the context of pulmonary diseases and explore their potential implications for epigenetic therapies.